Role of Bacteria in chronic Suppurative Otitis Media and Sensitivity pattern in Baqubah Teaching Hospital - Nasser Khalil Muhammed; Hayder Jasim Hamood (Diyala Journal of Medicine, 2019)
Background: Otitis media is an inflamation of middle ear, it is either acute or chronic,chronic may be otitis media with effusion(intact tympanic membrane) or may be chronic suppuratve otitis media(there is a perforation in the eardrum)which is aninflamation of middle ear mucosa and mastoid air cells for a period more than 3 months. This inflamation is either a sequely of acute suppurative otitis media (tubotympanic disease)or  may be due to a cholesteatoma(atticoantral disease).